Management of Tracheobronchial Injuries - Altinok, Tamer (Eurasian J Med, 2014)
Tracheobronchial injury is one of cases which are relatively uncommon, but must be suspected to make the diagnosis and managed immediately. In such a case, primary initial goals are to stabilize the airway and localize the injury and then determine its extend. These can be possible mostly with flexible bronchoscopy conducted by a surgeon who can repair the injury. Most of the penetrating injuries occur in the cervical region. On the other hand, most of the blunt injuries occur in the distal trachea and right main bronchus and they can be best approached by right posterolateral thoracotomy. The selection of the manner and time of approaching depends on the existence and severity of additional injuries. Most of the injuries can be restored by deploying simple techniques such as individual sutures, while some of them requires complex reconstruction techniques. Apart from paying attention to the pulmonary toilet, follow-up is crucial for determination of anastomotic technique or stenosis. Conservative treatment may be considered an option with a high probability of success in patients meeting the criteria, especially in patients with iatrogenic tracheobronchial injury.